2013
DOI: 10.1088/1674-1056/22/1/014304
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a bubble and a bubble cluster in an ultrasonic field

Abstract: Using an appropriate approximation, we have formulated the interacting equation of multi-bubble motion for a system of a single bubble and a spherical bubble cluster. The behavior of the bubbles is observed in coupled and uncoupled states. The oscillation of bubbles inside the cluster is in a coupled state. The numerical simulation demonstrates that the secondary Bjerknes force can be influenced by the number density, initial radius, distance, driving frequency, and amplitude of ultrasound. However, if a bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Yasui obtained a similar result through numerical simulations of radial pulsations in multi-bubble environment by assuming that the ambient radius of each bubble is the same for all the bubbles and by introducing a new variable named the coupling strengths ( , where is the distance from the bubble numbered i ) [14] , [15] , [16] , [17] . Wang formulated an interacting equation of multi-bubble motion for a system of a single bubble and a spherical bubble cluster, and found that the maximum radius of a bubble is suppressed and the suppression is enhanced as the bubble density increases [18] , which confirmed the result achieved by Yasui. The numerical simulation obtained by An suggested that the interaction between bubbles suppresses bubble expansion and the violent extent of the bubble collapse by analyzing the characteristics of cavitation in acoustic standing waves [19] .…”
Section: Introductionsupporting
confidence: 67%
“…Yasui obtained a similar result through numerical simulations of radial pulsations in multi-bubble environment by assuming that the ambient radius of each bubble is the same for all the bubbles and by introducing a new variable named the coupling strengths ( , where is the distance from the bubble numbered i ) [14] , [15] , [16] , [17] . Wang formulated an interacting equation of multi-bubble motion for a system of a single bubble and a spherical bubble cluster, and found that the maximum radius of a bubble is suppressed and the suppression is enhanced as the bubble density increases [18] , which confirmed the result achieved by Yasui. The numerical simulation obtained by An suggested that the interaction between bubbles suppresses bubble expansion and the violent extent of the bubble collapse by analyzing the characteristics of cavitation in acoustic standing waves [19] .…”
Section: Introductionsupporting
confidence: 67%
“…For instance, the lattice Boltzmann method [80] , which is an approach in between continuum dynamics simulations and MD simulations, may have great potential to study the collective effect [81] in the dissolving and formation process of surface nanobubbles [33] . This kind of studies would certainly deepen our understanding on cavitation and bubble nucleation and collapse [82][83][84][85][86][87] .…”
Section: Discussionmentioning
confidence: 99%
“…When the bubble chain is far enough away from the cluster, the secondary radiation pressure on the nearest bubble can be approximated as where is the bubble separation distance. Therefore, the dynamic equation of the bubble in the chain can be approximated as where is the liquid pressure on the bubble wall, is the van der Waals hard-core radius [38] , is the polytropic exponent, P 0 is the hydrostatic pressure, and , , and c are the liquid surface tension, viscosity, and sound speed, respectively. P a and f are the pressure amplitude and frequency of the external acoustic field, respectively.…”
Section: Theoretical Cavitation Structure Modelmentioning
confidence: 99%
“…Fig. 8 presents the secondary Bjerknes force ( F B2 ) using a grayscale color range in the R 10 – R 20 plane [34] by setting f = 20 kHz, D = 2 mm, N 1 = 10 3 [38] , and P a = 1.2 and 1.4 atm. The lighter and darker regions represent positive or negative values of F B 2 , respectively.…”
Section: Numerical Analysismentioning
confidence: 99%